Horner syndrome as a postoperative complication after minimally invasive video-assisted thyroidectomy: A case report. Issue 48 (December 2017) - Hu, Xiaolei; Zhang, Xiaomei; Gan, Huaiyong; Yu, Dajun; Sun, Weihua; Shi, Zhaoming
Abstract: Rationale: Horner syndrome is an unusual complication after thyroidectomy. Patient concerns: We report a case of Horner syndrome in a 34-year-old female patient with Graves disease associated with papillary thyroid carcinoma who underwent left-side minimally invasive video-assisted thyroidectomy and neck dissection. Diagnosis: Horner syndrome was diagnosed based on left myosis, eyelid ptosis, and mild enophthalmos, which developed in the patient on postoperative day 2. Interventions: The patient was administered glucocorticoids and neurotrophic drugs on postoperative day 3. Outcome: The symptoms of Horner syndrome were significantly relieved 1 year later. Lessons: Surgeons must be aware that Horner syndrome may be a source of iatrogenic complications, and patients also should be informed of these complications before surgery.